2016
DOI: 10.4236/fns.2016.76041
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Partial Fat Replacement by Whey Protein, Oat, Wheat Germ and Modified Starch on Sensory Properties, Viscosity and Antioxidant Activity of Reduced Fat Ice Cream

Abstract: Several studies are conducted to improve nutritional enrichment of ice cream. The aim of the present study was to produce healthy ice cream by partial replacement of fat with whey protein (WP), dietary fibers (oat (OT) and wheat germs (WG)) and modified starch (MS). Reduced fat ice cream (8% fat) was prepared as control. Healthy reduced fat ice cream was prepared by replacing 1% and 2% of fat with WP, OT, WG and MS. The fat replacement with OT and WG increased the fiber content of ice cream. In addition, ice c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 18 publications
4
15
0
Order By: Relevance
“…The melt-down rate of ice cream is affected by many factors, including the amount of air incorporated, the nature of the ice crystals and the network of fat globules formed during freezing. These results agree with result obtained by Marshall, et al, 2003, Goff and Hartel , 2013and Salem et al, 2016.…”
Section: Melting Rate%supporting
confidence: 93%
See 2 more Smart Citations
“…The melt-down rate of ice cream is affected by many factors, including the amount of air incorporated, the nature of the ice crystals and the network of fat globules formed during freezing. These results agree with result obtained by Marshall, et al, 2003, Goff and Hartel , 2013and Salem et al, 2016.…”
Section: Melting Rate%supporting
confidence: 93%
“…The fact that the constituents of ice cream are almost complete the highest Cutely assimilated makes ice cream an especially desirable food for growing children and for persons who need to maintain or put on weight, for example the elderly. For the same reason, though, portion control is essential for persons who need to reduce or who do not wish to gain weight, so that it becomes part of a balanced and healthy diet and the contribution it makes to energy Goff and Hartel (2013) and Salem et al, (2016).…”
Section: Physical and Chemical Properties Of Grains Cultivars And Thementioning
confidence: 99%
See 1 more Smart Citation
“…The shelf life of gum confection made from starch increase due to great stability and resistance to stirring. According to Salem et al [22], the modified starches by acetylation-oxidation also gives the characteristic taste and appearance better than acid-modified starch.…”
Section: Sensory Properties Of Marshmallow Creammentioning
confidence: 99%
“…() found that the viscoelasticity of WPI‐cross‐linked waxy maize starch mixed gels increased with an increase in the starch concentration at pH 7.00 in the presence of 100 m m NaCl. WPI and starch mixtures have recently been widely used in food applications (Cheong et al ., ; Pang et al ., ; Salem et al ., ).…”
Section: Introductionmentioning
confidence: 97%